The Life of Lazarillo of Tormes: His Fortunes and Misfortunes as Told by Himself - Anonymous; Luna, Juan de; Rudder, Robert S. (Salt Lake City, UT : Project Gutenberg, 1996)
"The Life of Lazarillo of Tormes: His Fortunes and Misfortunes as Told by Himself" is a Spanish novella published anonymously in 1554. Young Lázaro serves a succession of masters from a cunning blind beggar to various church officials learning survival through wit and deception in a harsh world. This groundbreaking work founded the picaresque genre, presenting society through a rogue's eyes rather than noble heroes. Its vivid portrayal of poverty and biting satire of religious hypocrisy led to its ban by the Spanish Inquisition, yet it influenced countless works from "Tom Jones" to "Huckleberry Finn." (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lazarillo_de_Tormes
Release date is 1996-02-01
Produced by an anonymous Project Gutenberg volunteer
Keywords: Spain -- Social conditions -- 16th century -- Fiction; Picaresque literature, Spanish; Spanish fiction -- Translations into English